KAJIAN KEBERLANJUTAN PERIKANAN CAKALANG (KATSUWONUS PELAMIS) DI BITUNG - Asia Asia; Heru Santoso; Yuli Purwanto; Johnny Tumiwa; Mohammad Zaini (JURNAL BLUEFIN FISHERIES, 2019)
Cakalang City is a nickname for the city of Bitung which is one of the Minapolitan areas and industrialization of capture fisheries in Indonesia. The purpose of this study is to assess the sustainability status of the Cakalang fisheries in Bitung and develop a strategy for managing the Cakalang fisheries in Bitung to be sustainable. Analysis of existing conditions and indexes for each dimension of sustainable management of skipjack resources, including ecological, economic, social, institutional and technological dimensions is carried out using the Multidimensional Scaling (MDS) approach with ordination techniques modified from the Rapfish program. The sustainability of cakalang fisheries in Bitung at 65.82 percent is in the fairly sustainable category (ecological dimension 46.46 percent, economic dimension 80.01 percent, technology dimension 65.83 percent, and institutional dimensions 58.57 percent), sustainability analysis shows Multidimensional sustainability index values indicate the sustainability status of the skipjack fisheries in Bitung is in a fairly sustainable category. Keywords: Bitung, skipjack, sustainability.